Shoulder impingement in overhead athletes: An uncommon complication of distal clavicle fracture - Corvino, A.; Catelli, A.; Corvino, F.; Tafuri, D. (Journal of Human Sport & Exercise, 2021)
Impingement syndrome is one of the most common pain disorders of the shoulder. The causes are numerous and most frequently it is due to structural alterations of coracoacromial arch; however, in in rare cases it may be caused by malunion of distal clavicle fractures. We report our experience in the case of a young tennis player with shoulder impingement after a conservative management of distal clavicle fracture.